The effect of heart rate on the heart rate variability response to autonomic interventions - Billman, George E. (Frontiers in Physiology, 2013)
Heart rate variability (HRV), the beat-to-beat variation in either heart rate (HR) or heart period (R-R interval), has become a popular clinical and investigational tool to quantify cardiac autonomic regulation. However, it is not widely appreciated that, due to the inverse curvilinear relationship between HR and R-R interval, HR per se can profoundly influence HRV. It is, therefore, critical to correct HRV for the prevailing HR particularly, as HR changes in response to autonomic neural activation or inhibition. The present study evaluated the effects of HR on the HRV response to autonomic interventions that either increased (submaximal exercise, n = 25 or baroreceptor reflex activation, n = 20) or reduced (pharmacological blockade: β-adrenergic receptor, muscarinic receptor antagonists alone and in combination, n = 25, or bilateral cervical vagotomy, n = 9) autonomic neural activity in a canine model. Both total (RR interval standard deviation, RRSD) and the high frequency variability (HF, 0.2 to 1.04 Hz) were determined before and in response to an autonomic intervention. All interventions that reduced or abolished cardiac parasympathetic regulation provoked large reductions in HRV even after HR correction [division by mean RRsec or (mean RRsec)2 for RRSD and HF, respectively] while interventions that reduced HR yielded mixed results. β-adrenergic receptor blockade reduced HRV (RRSD but not HF) while both RRSD and HF increased in response to increases in arterial blood (baroreceptor reflex activation) even after HR correction. These data suggest that the physiological basis for HRV is revealed after correction for prevailing HR and, further, that cardiac parasympathetic activity is responsible for a major portion of the HRV in the dog.